Educação ambiental e práticas sustentáveis na educação a distância - FERREIRA, Andreza Priscila de Lima (2017)
The consequences of environmental degradation are increasingly evident. For years it was already apparent that the model of economic development adopted was unsustainable. In this context, the individual is an active and passive subject in the relation between man and nature, while acting as an agent modifying the environment, degrading, it suffers the consequences of degradation and acts also looking for ways to reverse the situation. In this quest, one perceives the need of reflection of the individual and of the collective entity on its actions in the environment. Thus, attention is drawn to the development of environmental education as an alternative to interfere in this reality, encouraging reflection, awareness and awareness of society. In this scenario, the university, as a trainer and social influencer, must act in favor of the development of environmental education in the academic environment, contributing to the development of a society more conscious of its actions on the environment. However, according to the literature, these institutions have little progress regarding the development of sustainability. In this case, the promotion of punctual environmental education actions is carried out, most of which are carried out by research projects and the extension of teachers. Thus, the present study falls within this context of environmental and social responsibility of the university. The purpose of this study is to analyze the contributions of e-learning and m-learning in raising awareness about environmental issues in order to influence the behavior of the conscious consumption in the poles and headquarters of an academic unit of distance education of a Brazilian public university. The study is set up as action research and consisted of three phases: recognition, diagnosis and intervention; According to model ANISE (Análisis de las Necesidades de Intervención Sócioeducativas). For the data analysis, qualitative and quantitative methods were used. The results show that environmental education interventions developed throughout the research not only had a good receptivity of the academic community in the study environment, but are also necessary and should be continuous to stimulate the reflection on the need to change behavior consumption. It was confirmed that environmental education actions can be favored by the use of Distance Education and technologies, e-learning and m-learning, to encourage conscious consumption in the university of paper, disposable cup, energy and water. It was seen that in this environment, e-learning is well accepted as a training tool and encourages awareness of the social role of the individual in the face of environmental issues. Thus, it is accepted that the possibilities of education and training offered by Distance Education with the use of technologies, can contribute to the construction of a new reality and present itself as tools in the development of environmental education.